Gestion intégrée de l’eau et changements globaux face aux logiques de l’action administrative locale - Elias Ganivet; Véronique Van Tilbeurgh; Mélanie Congretel; Laurent Longuevergne (VertigO, 2024)
In France, over the last decades, public authorities seems to have promoted (through the orientation of regulatory texts) an « integrated water resource management ». The implementation of this approach has resulted, in particular, in the transfer of numerous competences to dedicated departments of local authorities and to their groupings. At the same time, water resources are under increasing threat from a host of anthropogenic pressures - otherwise known as "global change". In this context, our study aims at exploring how the local implementation of water management - which has resulted in a segmented approach - is articulated with a management under increasing pressures from global change. This articulation was explored inside a local authority ‒ the conurbation of Lorient Agglomération. Between the consideration of local specificities, the hydro-climatic changes, and the logic of local administrative action, it emerged that water management remains organized into different sectors (drinking-water/sanitation, urbanism, aquatic ecosystems) and is marked by a technical-administrative approach – mostly guided through the application of regulatory procedures, to the detriment of a transversal management integrating local stakeholders. Such conclusion is even more problematic given that climate-related pressures have so far been insufficiently taken into account in planning documents. While the lack of transversality did not seem to pose a major problem in a context of abundance, it is proving particularly inappropriate to the new hydro-climatic context ‒ imposing a constrained transversality.